Automated Construction System of Robot Locomotion and Operation Platform for Hazardous Environments— Basic System Design and Feasibility Study of Module Transferring and Connecting Motions1. Issue 6 (4th February 2015) - Fukui, Rui; Kato, Yuta; Takahashi, Ryo; Wan, Weiwei; Nakao, Masayuki
Abstract : Unmanned robot operation is highly anticipated for use in hazardous environments such as a nuclear accident and mine accident sites. We propose an automated construction system for robot locomotion and operation platform in a severely disturbed environment. In such an environment, the sensors and actuators that can be used are restricted. The platform is intended to enable specialized working robots to have access to any cube‐diced operation point, and to build a rail both for the platform itself and for specialized working robots. The entire platform structure is modularized, which means that the structure comprises multiple modules. They are assembled and constructed through cooperation of a transfer robot and a constructor robot. This paper describes the development of prototypes and explains experiments conducted to verify our fundamental concept. In particular, the feasibility of module‐transfer and connection motions in three prioritized positions is verified using the developed prototypes. The system design and experiments reveal that the most important technique to realize the proposed system is how to use guide structures to reduce the effects of mechanical error and misalignment among robots.